Anti-doping sciences, abjection and women’s sport as a protected category - Schneider, Angela J.; Oldham, Alan C.; Butcher, Loughran H. G. (Frontiers in Sports and Active Living, 2023)
In this article we explore the relationships amongst anti-doping sciences, ‘abjection,’ and the protection of ‘women’s’ sport. The debate concerning participation in women’s sport—especially elite sport—of people who do not fit within the traditional definitions is increasingly fraught with acrimony and the anti-doping sciences have been recruited at times to be used to arbitrate. Emotions tend to run high in arguments that typically center on inclusion gender diverse (TGD) athletes on the one hand or protection of the women’s category on the other hand. While sport theorists have begun the important work of identifying the roots of these problems deep within the structure of modern sport and society itself, they have hitherto paid little attention to the philosophical underpinnings of that structure. In particular, this paper seeks to understand the complex role of ‘abjection’ in framing the current debate in sport and in related anti-doping sciences. From a clear definition of abjection as a perceived existential threat due to violation of the status quo, we introduce a new theoretical concept, ‘abjection bias’, as a means of understanding and explaining what might have used to be called ‘gut reaction’. By looking at the only two previous treatments of sport abjection and highlighting the historical connections between anti-doping sciences and efforts to protect the women’s category, we demonstrate that this co-development is, in part, more easily understood in the context of ‘abjection’. We conclude that the clarity gained from understanding this reasoning and the role of abjection and abjection bias can also help to shed light on current policy decision-making in relation to the question of protecting the women’s sport category.